Understanding the factors associated with child malnutrition in rural Burundi: experiences from the Muyinga and Ngozi provinces - Emera, Willy Désiré; D’Haese, Marijke; Slosse, Wannes; Lachat, Carl (Taylor & Francis, 2025)
Background: Childhood stunting, wasting, and underweight are markers of poor nutrition and socioeconomic deprivation in low-income countries. It remains unclear which factors are associated with child malnutrition in rural Burundi, in particular in a context of subsistence farming as found in rural Burundi.Aim: This study investigates child undernutrition in rural Burundi and identifies household-level risk factors in subsistence farm households.Method: A sample of 242 children participated in a cross-sectional survey conducted in Muyinga and Ngozi provinces. Height-for-age z-scores (HAZ), weight-for-age z-scores (WAZ) and weight-for-height z-scores (WHZ) were calculated using the WHO Anthro Survey Analyser. Descriptive and regression analyses were used to identify factors associated with a child’s risk of stunting (children with a HAZ < −2 standard deviation [SD]), underweight (children with a WAZ < −2SD) and wasting (children with a WHZ < −2SD).Results: A high prevalence of stunting was found (in 53.1% of children under 5 years of age) in our sample. About a quarter of the children in the sample (25.1%) were underweight and 8.9% were wasted. The presence of off-farm income in the household of the children was associated with a lower prevalence of underweight and wasting. Households whose earnings were more than US$238 in the season prior to the survey were less likely to have a child who was underweight (OR = 0.05; CI: 0.00–0.32; p = 0.009) than households whose earnings were less than US$96 in that season, but children were equally likely to suffer from stunting. No evidence was found that children from households that were able to sell more of their produce were less malnourished.Conclusion: In the context of subsistence farming, self-consumption of agricultural produce is insufficient to support optimal growth of children under the age of 5. Diversifying household income sources could contribute to improve the children’s nutritional status in the short run.